SHUKUR XOLMIRZAYEV ASARLARIDA MILLIY RUH VA QADRIYATLAR (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the artistic interpretation of the national spirit and values ​​in the prose works of the people's writer of Uzbekistan Shukur Kholmirzayev. The writer's stories and tales, such as "Uzbeks", "Unknown Man", "Bird Language", "Uzbek Grandfather", "Navruz, Navruz...", deeply reveal the ideas of the Uzbek people about their simplicity, hospitality, tolerance, honesty, harmony with nature, and understanding of national identity through traditions and folklore. The study shows the realistic style of the writer's work, the Surkhandarya color, and the preservation of the national spirit against the background of modern social problems. The results confirm that Kholmirzayev's works serve as an important source in the education of national values ​​​​during the period of independence.